Europec 2015 2015
DOI: 10.2118/174310-ms
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Assisted History Matching Using Binary Image Matching

Abstract: This paper presents a history matching scheme that has been applied to production data and time lapse seismic data. The production data objective function is calculated using the conventional least squares method between the historical production data and simulation predictions, while the seismic objective function uses the Hamming distance between two binary images of the gas distribution (presence of gas (1) or absence of gas (0)) sequenced over the different acquisition times. The technique is applied to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…We know from laboratory experiments that free gas is known to have a substantial effect on seismic wave properties (Han and Batzle ,b), however, the impact of the gaseous phase could potentially be counteracted by the oil now becoming less ‘lively’ due to the loss of the lighter gas components. To understand whether this contribution is significant, Obidegwu () modelled the fluid properties of the oil–gas mixture by taking into account the effect of the released gas in API and the gas–oil ratio (Rs) and compared them to the fluid properties of the oil–gas mixture ignoring these oil changes, and found that fluid substitution calculations and resultant interpretations can ignore the oil phase changes to first order. Hence, in our calculations of fluid substitution, the oil properties remain constant.…”
Section: Modelling Scale Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We know from laboratory experiments that free gas is known to have a substantial effect on seismic wave properties (Han and Batzle ,b), however, the impact of the gaseous phase could potentially be counteracted by the oil now becoming less ‘lively’ due to the loss of the lighter gas components. To understand whether this contribution is significant, Obidegwu () modelled the fluid properties of the oil–gas mixture by taking into account the effect of the released gas in API and the gas–oil ratio (Rs) and compared them to the fluid properties of the oil–gas mixture ignoring these oil changes, and found that fluid substitution calculations and resultant interpretations can ignore the oil phase changes to first order. Hence, in our calculations of fluid substitution, the oil properties remain constant.…”
Section: Modelling Scale Effectsmentioning
confidence: 99%
“…(b) Pressure depletion condition in the oil leg, with the field pressure dropping below the bubble point. As pressure decreases below the bubble point, the gas saturation builds progressively as gas bubbles are first nucleated, and then coalesce or grow more by the diffusion of additional free gas (Falahat et al 2014;Obidegwu 2015). When a significant number of bubbles are liberated, the fluid system reaches the critical gas saturation, for which the gas becomes mobile.…”
Section: Saturation and Pressure Scenariosmentioning
confidence: 99%
“…Even though there are a number of general mitigation techniques (e.g., localization [7] and inflation [30]) available, each of them has its own drawbacks limiting its efficiency in real applications [29]. Some recent research has been focused on seeking a sparse representation efficiently reducing the number of original data while still capturing the essential information contained in the data [54,40,33,57].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2015) compared the area of the CO 2 plumes instead of the quantitative CO 2 saturations for the Sleipner benchmark model because the simulated CO 2 saturations are not fairly matched to the observed CO 2 saturations. Obidegwu et al (2015) measured the dissimilarity between binary images of gas distributions obtained from seismic data using the Hamming distance (Hamming, 1950).…”
Section: Introductionmentioning
confidence: 99%